1988
DOI: 10.1111/j.1600-0404.1988.tb05925.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal immunoglobulin bands in cerebrospinal fluid of patients with Alzheimer's disease and vascular dementia

Abstract: We examined serum and cerebrospinal fluid (CSF) of 16 patients with Alzheimer's disease (AD), 28 patients with vascular dementia (VD), their age-matched controls and multiple sclerosis (MS) patients in order to evaluate the humoral immune response within the central nervous system both quantitatively and qualitatively. Intra-blood-brain barrier (BBB) protein synthesis was calculated by CSF IgG index. The presence of oligoclonal banding (OCB) was investigated with agarose isoelectric focusing (IEF) followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
3
9
0
1
Order By: Relevance
“…This is in agreement with a few previous studies on PDD [3][4][5][6], but contradictory to several oth ers [7][8][9][10][11][12][13]. The frequency of intrathecal IgG synthesis in PDD patients is rather small, but was revealed in the present study probably because of the large number of patients in comparison with other studies.…”
Section: Intrathecal Synthesis O F Igg In Pddsupporting
confidence: 38%
See 1 more Smart Citation
“…This is in agreement with a few previous studies on PDD [3][4][5][6], but contradictory to several oth ers [7][8][9][10][11][12][13]. The frequency of intrathecal IgG synthesis in PDD patients is rather small, but was revealed in the present study probably because of the large number of patients in comparison with other studies.…”
Section: Intrathecal Synthesis O F Igg In Pddsupporting
confidence: 38%
“…Primary degenerative dementia (PDD; Alzheimer's disease) is a brain disorder charcterized by progressive impairment of memory and other cognitive functions in combination with loss of nerve cells, presence of neuritic plaques and neurofibrillary tangles [1], The etiology of PDD is unknown, but several studies have suggested that dysfunction of the immune system may play a role in the etiology of the disease [for a review see 2], This sugges tion has been supported by the occurrence of oligoclonal immunoglobulin G (IgG) bands in the cerebrospinal fluid (CSF) of patients with PDD [3][4][5][6], However, sev eral other studies have yielded contradictory results, i.e., no evidence of intrathecal IgG synthesis in PDD patients [7][8][9][10][11][12][13], This contradiction induced us to carry out the present study, using a large group of well-defined PDD patients and a large group of healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the occurrence of CNS specific OCB in the CSF of patients with Alzheimer's disease was first reported in 1980 [16] this and subsequent reports have only evaluated relatively small numbers of patients [1,5,10] [3,4,7,8]. The presence of OCB in primary neurodegenerative dementia is generally considered to be a rarity such that their absence is supportive of diagnosis, specifically for example of probable AD [13].…”
Section: Introductionmentioning
confidence: 95%
“…This would support hypotheses concerning the involvement of infectious agents or abnormalities of the immune system in the etiology of AD 115 , 116 . This contention, however, is not supported by results of either conventional electrophoresis, agarose isoelectric focussing, or two‐dimensional polyacrylamide gel electrophoresis, all of which failed to show oligoclonal banding in CSF of AD patients 111 , 117–119 . Furthermore, the fact that CSF/serum IgG ratios and IgG indices, representing quantification of intrathecal IgG synthesis, are not changed in AD also contradicts the concept of CNS IgG production in AD 104–106 , 109–111 , 120 .…”
Section: Amino Acids and Proteinsmentioning
confidence: 73%
“…Albumin and Immunoglobulins Increased absolute amounts of albumin in CSF of AD patients as well as elevated CSF/serum albumin ratios support the concept of blood‐brain barrier dysfunction in AD 104–107 . However, the notion of increased blood‐brain barrier permeability remains controversial because various investigators could not reproduce the finding of (relatively) increased CSF albumin in AD, 48 , 49 , 80 , 108–111 and Rozemuller et al 112 could not demonstrate plasma proteins in the neuropil of a number of AD patients. Recently, Blennow et al 113 were able to identify increased CSF/serum ratios for albumin only in those AD patients with risk factors for small vessel disease (hypertension, diabetes mellitus, history of ischemic heart disease).…”
Section: Amino Acids and Proteinsmentioning
confidence: 99%